The Impact of Self-Efficacy Analysis-Based Psychological Theory and Literary Ethics on Chinese American Entrepreneurship Education - Li, Hang; Wang, Junsheng; Zhang, Yunyu; Li, Hongmei; Chen, Xialu (Frontiers in Psychology, 2020)
To study the entrepreneurial behavior of Chinese American college students, the entrepreneurship education is explored from the perspective of the combination of psychology and literary ethics, thereby promoting the development of entrepreneurship education. Based on the analysis of self-efficacy, the correlations among entrepreneurial intention, entrepreneurship education, and entrepreneurial efficacy of the research samples are analyzed. First, through the questionnaire design, the research samples and the measurement scales of each research variable are determined, and the survey results and the reliability of the scale are analyzed and tested. Second, based on the variance analysis and regression analysis methods, a descriptive statistical analysis is performed on the correlations among entrepreneurship education, entrepreneurial intentions, and entrepreneurial efficacy among Chinese American college students. Finally, based on the constructed correlation structure model, the intermediary role of entrepreneurial efficacy in entrepreneurship education and entrepreneurial intention is tested. Besides, the individual gender and family entrepreneurial behaviors are considered. The results show that the valid rate of questionnaire is good, which is 96.49%; the reliability and validity of the scales of the research variables are good; the Cronbach’s Alpha reliability coefficient values are all above 0.80; the fitting results of the confirmatory factors are good. The regression analysis results show significant correlations among entrepreneurship education, entrepreneurial intentions, and entrepreneurial efficacy among Chinese American college students. Entrepreneurial efficacy has a partially intermediary role in the two dimensions of entrepreneurship education and entrepreneurial intention. Individual gender and family entrepreneurial behaviors have moderating impacts on the entrepreneurial efficacy levels of college entrepreneurs. From the perspectives of psychology and literary ethics, the above results have positive effects on the development of entrepreneurship education.